Managing banking risks - Cade, Eddie (Chicago : Glenlake Pub. co. ; New York : AMACOM, 1999)
This publication is risk planning manual that covers the full range of banking risks operations managers and executives need to understand, including solvency risk, liquidity risk, credit risk, interest rate risk, price risk, operating risk, and more. The book shows how to manage each of the kinds of risk effectively within the total banking context and structure and examines in detail such issues as volatility, expected and unexpected loss, the role of risk capital, rate of return, and required reward for risk.
1. Risk and reward --2. What are the banking risks? --3. Solvency risk --4. Liquidity risk --5. Credit risk: policy overview --6. Credit risk: analysing the portfolio --7. Credit risk: changing the portfolio --8. Interest rate risk: structural exposure --9. Interest rate risk: trading exposure --10. Price risks --11. Operating risks --12. Conclusion: organising risk management.
Includes bibliographical references (p. 227-228) and index.
lje 02/05/13
Loan
Keywords: Risk management; Bank management